Is it French? Popular Postnational Screen Fiction from France - Harrod, Mary; Moine, Raphaëlle (Palgrave European Film and Media Studies,, 2023)
This book investigates the recently accelerated phenomenon of mainstream French film and serial television's remarkable popularity not only within but - more novelly for European audiovisual narratives - outside the domestic context. Treating changes that have taken place in France's production landscape during the mass rollout of global streaming platforms as revelatory of broader tendencies in media production and circulation in Europe and beyond, the collection explores emergent influential players (Omar Sy, Camille Cottin, Alexandre Aja and Fanny Herrero), companies such as Netflix and Gaumont, and new genres, identities and representations on screen. It thus draws together a body of new research by international experts in French and European media production to analyse popular film and television series from France through a postnational lens with regards to both economic and institutional norms and to culture as a whole.